Richard Ovenden, Burning the Books: A History of Knowledge Under Attack. London: John Murray (2020) - Brown, Katherine E (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2022)
Richard Ovenden, Burning the Books: A History of Knowledge Under Attack. London: John Murray (2020)